Demografski i društveni razvoj Martinaca u 18. i 19. stoljeću - Vegh, Andor (SlavVaria, 2022)
Demographic and social development of Martinci/Felsőszentmárton in the 18th and 19th centuries. In this paper the author investigates the way the Croatian minority village community was formed at the end of the 18th and in the first half of the 19th century. Through the quantitative analysis of birth register data and the qualitative analysis of surnames in the aforementioned databases of the village of Martinci / Felsőszentmárton, the author creates a picture of the formation of society and community in the 19th century. With the help of published literature, the author provides a summary of the issue of im-migration, which formed the basis of further development and modernization, the stages of which the author determines using the methods of social, demo-graphic and historical research.